Natural polyphenolic coffee extract administration relieves chronic nociplastic pain in a reserpine‐induced fibromyalgia‐like female mouse model - Rubén Toledano‐Martos; Anna Bagó‐Mas; Meritxell Deulofeu; Judit Homs; Núria Fiol; Enrique Verdú; Pere Boadas‐Vaello (Brain and Behavior, 2024)
Abstract Introduction Nociplastic pain involves reflexive and nonreflexive pain responses and it is a core symptom of fibromyalgia (FM). The increasing prevalence of this health condition and the low rates of patients’ quality of life, combined with the lack of suitable pharmacologic treatments, evidence the demand to research new alternatives. Polyphenols may be potential therapeutic candidates as they have been reported to exert pathological pain modulation in preclinical models. In that context, this work was aimed to study the antinociceptive effects of a polyphenolic extract obtained from decaffeinated ground roasted coffee, in the RIM6 FM‐like mouse model. Methods To this end, RIM6 adult ICR‐CD1 female mice were administered daily once a week with either 10 or 15 mg/kg of extract, and reflexive pain responses were evaluated for up to 3 weeks. At the end, the depressive‐like behavior was assessed as a nonreflexive pain response, and spinal cord and serum samples were collected for immunohistochemical and toxicological analyses. Results These findings showed that the repeated administration of the coffee polyphenolic extract (CE) modulated reflexive pain responses, depressive‐like behavior, and spinal cord gliosis in a dose‐dependent manner, without signs of systemic toxicity. Conclusion Thus, the CE may be a potential pharmacological treatment suitable to relieve nociplastic pain responses characteristic of FM.